Design of a Modern Car Parking at the Faculty of Engineering, Technology Aplied Design and Fine Art. - Byamukama, Samuel (Kabale University, 2023)
The ever-increasing use of the faculty green land as a parking lot for vehicles called for our group to research and designs a modern car ark. The investigated the most feasible solution of keeping in lace equal ratio of green land to buildings in the existence. To achieve this, we designed a ground plan, model using arch cad and hand molded a prototype using mounting boards, novice glue, to show what we exactly designed using the software. Chapter one about introduction explains the basis of the faculty, back ground of the project, problem statement, specific objective, main objectives . Chapter two explains the basis of our research, study and source of the knowledge of our design. Chapter three gives an overview of the employed methods that helped us to come find feasible solution to the problem statement. It includes bench marking, data collection, and design among the many Lastly chapter four explains the future works, conclusions and recommendations.